ANALISIS PENCATATAN DAN PELAPORAN KEUANGAN PADA SATUAN KERJA PERANGKAT DAERAH (SKPD) BERDASARKAN PERMENDAGRI NOMOR 64 TAHUN 2013 DI PEMERINTAH KOTA MANADO - Tarigan, Desriani N.; Mawikere, Lidia M. (Universitas Sam Ratulangi, 2016)
Local Government financial statements are prepared to provide relevant information about the financial position and all transactions carried out by the Local Government during the reporting period. The purpose of this study was to determine whether SKPD Badan Pelaksana Penyuluhan dan Ketahanan Pangan Manado City has been taking notes and preparing financial reporting by Regulation No. 64 of 2013. The analytical method used is descriptive method with qualitative and quantitative data collection in order to understand the data. The results showed SKPD Badan Pelaksana Penyuluhan dan Ketahanan Pangan Manado City in Fiscal Year 2015 to apply accrual accounting system based on Regulation No. 64 Year 2013. Keywords: Analysis, Recording, Reporting, Finance